Tumor extracellular vesicles drive metastasis (it's a long way from home). Issue 11 (6th August 2021) - Ghoroghi, Shima; Mary, Benjamin; Asokan, Nandini; Goetz, Jacky G.; Hyenne, Vincent
Abstract: Among a plethora of functions, extracellular vesicles released by primary tumors spread in the organism and reach distant organs where they can induce the formation of a premetastatic niche. This constitutes a favorable microenvironment for circulating tumor cells which facilitates their seeding and colonization. In this review, we describe the journey of extracellular vesicles (EVs) from the primary tumor to the future metastatic organ, with a focus on the mechanisms used by EVs to target organs with a specific tropism (i.e., organotropism). We then highlight important tumor EV cargos in the context of premetastatic niche formation and summarize their known effects on extracellular matrix remodeling, angiogenesis, vessel permeabilization, resident cell activation, recruitment of foreign cells, and ultimately the formation of a pro‐inflammatory and immuno‐tolerant microenvironment. Finally, we discuss current experimental limitations and remaining opened questions in light of metastatic diagnosis and potential therapies targeting PMN formation.